2017
DOI: 10.1186/s40463-017-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the mechanical properties of different skin sites for auricular and nasal reconstruction

Abstract: BackgroundAutologous and synthetic nasal and auricular frameworks require skin coverage. The surgeon’s decides on the appropriate skin coverage for reconstruction based on colour matching, subcutaneous tissue thickness, expertise and experience. One of the major complications of placing subcutaneous implants is the risk of extrusion (migration through the skin) and infection. However, knowledge of lessening the differential between the soft tissue and the framework can have important implications for extrusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 22 publications
0
48
0
1
Order By: Relevance
“…As indicated previously, skin tissue is inhomogeneous, anisotropic, and viscoelastic, and a wide range of elastic moduli have been reported in the literature, depending on age, anatomical site, and health status, as well as testing protocols and conditions. For the purpose of the present analyses, we assume that the elastic modulus of adult skin falls within the mid‐range of reported empirical data for hydrated human skin, which is 100 kPa for out‐of‐plane (eg, indentation or suction) mechanical loading 13,27‐31 . We further assume, based on reported experimental data, that the elastic modulus of skin increases by 50% (ie, to 150 kPa) with old age 32 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As indicated previously, skin tissue is inhomogeneous, anisotropic, and viscoelastic, and a wide range of elastic moduli have been reported in the literature, depending on age, anatomical site, and health status, as well as testing protocols and conditions. For the purpose of the present analyses, we assume that the elastic modulus of adult skin falls within the mid‐range of reported empirical data for hydrated human skin, which is 100 kPa for out‐of‐plane (eg, indentation or suction) mechanical loading 13,27‐31 . We further assume, based on reported experimental data, that the elastic modulus of skin increases by 50% (ie, to 150 kPa) with old age 32 .…”
Section: Resultsmentioning
confidence: 97%
“…For the purpose of the present analyses, we assume that the elastic modulus of adult skin falls within the mid-range of reported empirical data for hydrated human skin, which is 100 kPa for out-of-plane (eg, indentation or suction) mechanical loading. 13,[27][28][29][30][31] We further assume, based on reported experimental data, that the elastic modulus of skin increases by 50% (ie, to 150 kPa) with old age. 32 The elastic modulus of CLSP is approximated as that of its main component, cyanoacrylate, which is 200 MPa depending on the specific chemical formulation 33 ; there are various esters of cyanoacrylic acid in the different homologues.…”
Section: Contribution Of the Cyanoacrylate Coating Layer To The Flementioning
confidence: 99%
“… 181 Differences in mechanical properties are also suggested to depend on proteoglycan distribution within these layers, imparting a viscoelastic behavior based on the supramolecular assembly of these molecules. The mechanical properties of skin also differ at different locations of the body 187 and have in-plane anisotropy at different locations, 188 which correlates to changes in collagen and elastin content and overall ECM orientation. 189 This variety in tissue and different methods of evaluation produce measurements ranging from 0.02 to 58 MPa.…”
Section: Ectodermmentioning
confidence: 99%
“…Moreover, the Young's modulus values ranged from 0.002 to 0.06 MPa (Figure 2e) and are comparable to human skin, that is, wrist, abdomen, and forearm, where the Young's modulus varied from 0.003 to 0.2 MPa based on age and gender. [ 44,45 ] Overall, the toughness values of skin‐inspired substrates obtained from the data in Figure 2c showed that varying the loading ratio of stiff and elastic NFs in the skin‐inspired substrate can be tuned to absorb deformation energy without fracture (Figure 2f). Embedding stiff NFs only in PDMS resulted in toughness values of 410, 500, and 700 J⋅m −3 at loading ratios of 0.2:0:0, 0.4:0:0, and 0.6:0:0, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The tunability of the mechanical properties of the substrate allowed us to mimic different parts of humans within the initial toe region. [ 44,45 ] Interestingly, the layer of Au (50 nm)/Cr (3 nm) coated on the skin‐inspired substrate was electrically and mechanically stable after cyclic stretching up to 7000 cycles or during cyclic stretching at 35% strain, which indicates an effective absorption of stress by embedded SMNNs. The stability of the fabricated chemoresistive sensor device on the skin‐inspired substrate was also confirmed under stretched conditions up to 30% strain.…”
Section: Introductionmentioning
confidence: 99%